Dinamika Hukum Dalam Penyelesaian Sengketa Bisnis: Perspektif Konseling - Suparlan Suparlan; Munawirsazali Munawirsazali (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
Business dispute resolution is crucial for maintaining continuity and stability amid the complex and evolving business environment. This study examines dispute resolution mechanisms, focusing on counseling as a facilitative process that helps parties manage conflicts constructively and cooperatively. Using a qualitative approach with literature review and case analysis, the study explores counseling’s role in Indonesian business law. Findings show counseling accelerates dispute resolution with lower costs and time, preserves business relationships, and supports sustainability. Information technology, especially Online Dispute Resolution (ODR), enhances access to online counseling. The study recommends improving regulations, professional counselor training, and business community outreach to optimize counseling as an innovative solution for modern business dispute resolution.